The Atheist Bunyan: The Pilgrim’s Progress and Organized Freethought in Victorian Britain - Reagles, David (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2015)
This article explores how freethinkers received John Bunyan and read his works in Victorian Britain. An analysis of freethinking periodicals, letters to editors, lectures, essays, and autobiography reveals a vexed relationship that was anything but monolithic. There emerged two distinct reading communities within organized freethought. Some freethinkers, especially in the early nineteenth century, rejected Bunyan as another representation of irrational religious faith that was a hindrance to societal reform. However, other freethinkers appropriated his works and used him as a valuable resource for understanding their own experiences with religion as well as for communicating their message. I demonstrate that these contrasting positions resulted from interpretive strategies that stem from fundamental assumptions regarding how the project of secularism ought to interact with Britain’s predominantly Christian culture. It corresponds to an ongoing negotiation of meaning within organized freethought that reflects internal fissures, as well as a rapidly changing British society.